2015
DOI: 10.1515/jhsem-2014-0054
|View full text |Cite
|
Sign up to set email alerts
|

Coerced Confusion? Local Emergency Policy Implementation After September 11

Abstract: This study examines what motivates local emergency management officials to implement federal emergency management and homeland security policies within their own departments since the September 11 attacks. Pre-existing research claims there is confusion among local governments about potential changes to the role local emergency management services play before, during, and after natural, accidental, or terror related incidents. Meanwhile, additional research claims the federal disaster management policies (The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 44 publications
6
11
0
Order By: Relevance
“…In total 3554 valid e-mail addresses were found and distributed the survey, from which 775 (21.8%) responded, covering all 50 states. This response rate is very similar to a previous study by Hildebrand (2015Hildebrand ( , 2017Hildebrand ( , 2019, where the survey garnered 540 responses from 2422 (22.3%) in the sample pool of similar recipients but representing only 48 states during the summer of 2008. Additional nationwide web-based surveys in the emergency management field performed by Weaver et al (2014) and Wernstedt et al (2019) had similar response rates amongst local emergency management professionals at 30.3 and 17.1% respectively.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…In total 3554 valid e-mail addresses were found and distributed the survey, from which 775 (21.8%) responded, covering all 50 states. This response rate is very similar to a previous study by Hildebrand (2015Hildebrand ( , 2017Hildebrand ( , 2019, where the survey garnered 540 responses from 2422 (22.3%) in the sample pool of similar recipients but representing only 48 states during the summer of 2008. Additional nationwide web-based surveys in the emergency management field performed by Weaver et al (2014) and Wernstedt et al (2019) had similar response rates amongst local emergency management professionals at 30.3 and 17.1% respectively.…”
Section: Methodssupporting
confidence: 86%
“…Even though there seemed to be disappointment against the Obama administration amongst the local officials, it was not limited in Republican districts to just his administration. The results demonstrate a level of disconnect between the federal desires of both administrations and the desire of local actors to retain local control in emergency situations in a manner similar to that expressed in previous research (Birkland and Waterman 2008;Chang 2017;Edwards 2007;Esinger 2004;Haddow 2005;Hildebrand 2015;Hill and Hupe 2003;Jensen 2011;Jensen and Waugh 2014;Jensen and Youngs 2014;Lester and Krejci 2007;McEntire 2004;Newmann 2002;Nicholson 2007;Scavo, Kearney, and Kilroy 2008;Schneider 2005;Takeda and Helms 2006;Waugh 2006;Wise 2002). This suggests that the idea of local flexibility that the federal policies have on paper may have some fans, but the changes since the September 11 attacks still have many detractors, and they cross partisan lines in the jurisdictions they represent when expressing their dissatisfaction with the direction from the federal level.…”
Section: Discussion Of Hypotheses and Findingssupporting
confidence: 70%
See 1 more Smart Citation
“…Jensen and Youngs (2014) examine the implementation of the National Incident Management System (NIMS) at the county level. Hildebrand (2015;2017;2019) considered the opinions of local emergency management officials regarding federal policy demands that emanated after the September 11 attacks, such as NIMS, the National Response Plan (NRP) and its replacement policy the National Response Framework (NRF), as well as the Incident Command System (ICS). None of this work examines any impacts on the size of the county or the location (urban/rural/suburban) of the county or municipality specifically.…”
Section: Relevant Literature Review -Pandemic Planning and Emergency Managementmentioning
confidence: 99%
“…Research has shown that the federal government, while attempting to take the lead role during emergency situations, has been somewhat lax regarding the degree of enforcement of the federal policy and grant expectations (Jensen 2009 , 2010 , 2011 ; Hildebrand 2015 ). But, disagreement exists regarding federal policy expectations in this field.…”
Section: Introductionmentioning
confidence: 99%